Calcule underset(n -> + oo)(l i m) (a_n + 1)/(a_n) e underset(n -> + oo)(l i m) root(n)(a_n)

Letra b)

a_n = n

Passo 1

Quando a_n = n , o limite underset(n -> + oo)(l i m) (a_n + 1)/(a_n) será.

underset(n -> + oo)(l i m) (n + 1)/(n) = underset(n -> + oo)(l i m) (1 + (1)/(n))/(1) = 1

Portanto

underset(n -> + oo)(l i m) (a_n + 1)/(a_n) = 1

Passo 2

Para o limite com raiz

underset(n -> + oo)(l i m) root(n)(a_n) = underset(n -> + oo)(l i m) n^((1)/(n)) = 1

Então o limite quando a_n = n é

underset(n -> + oo)(l i m) root(n)(a_n) = 1

Resposta

underset(n -> + oo)(l i m) (a_n + 1)/(a_n) = 1

underset(n -> + oo)(l i m) root(n)(a_n) = 1

Ver Outros Exercícios desse livro